Relationship Between Orthorexia Nervosa, Eating Attitudes and Obsessive-Compulsive Disorder Among Nursing Students: A Cross-Sectional Study - Kaynar Demirel, Nur Sema; Ayhan, Cemile Hürrem; Aslan, Kadriye (The European Research Journal, 2026)
Objectives: This study aims to determine the levels of orthorexic tendencies, eating attitudes, and obsessive-compulsive symptoms in nursing students, examine the relationships among these variables, and investigate whether orthorexic tendencies and eating attitudes predict obsessive-compulsive symptoms. Methods: The study was designed as a descriptive, cross-sectional study. Participants were selected using purposive sampling. Descriptive Characteristics Information Form, Orthorexia-11 Scale, Eating Attitudes Test (EAT) and Padua Inventory-Washington State University Revision (PI-WSUR) scales were used. This study was reported in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology checklist for cross-sectional studies. Results: The mean score was 19.11±11.53 in the EAT participants, 28.30±4.16 in the Orthorexia-11 Scale and 56.35±23.85 in the PI-WSUR. A positive correlation was found between the participants’ orthorexia nervosa tendencies and obsessive-compulsive symptoms. It was observed that as the participants' EAT mean scores increased, their obsessive-compulsive symptoms also increased. In the regression analysis, it was seen that orthorexia nervosa tendencies and eating attitudes were significant predictors of obsessive-compulsive symptoms. Conclusions: The findings obtained from the study are important in terms of shedding light on the relationship between orthorexia nervosa, eating attitudes and obsessive-compulsive symptoms in nursing students. Given that health sciences students are a high-risk group for eating disorders, it is essential to include courses on eating disorders in the curriculum and implement regular psychological screenings in universities.